SYNDROMIC SURVEILLANCE: A POTENTIAL METHOD FOR ALTERNATIVE ANIMAL HEALTH SURVEILLANCE SYSTEM - Kardena, I Made (Buletin Veteriner Udayana; Vol 2 No. 1 Pebruari 2010)
Syndromic surveillance is an alternative surveillance system which can potentially detectanimal disease outbreaks in the early stages. Although syndromic surveillance haslimitations for the detection of sub-clinical and specific diseases, the method has the abilityto detect disease outbreaks rapidly including clinical emerging issues. In addition,syndromic surveillance is a suitable surveillance tool that can be applied in developingcountries since it is a low-cost surveillance method and is an option for poorly-resourcedveterinary services.
Keywords: Surveillance, Early stage monitoring, Epidemiology